Teaching English Vocabulary: What International Language Educators Tell Us - GUSTI ASTIKA (The English Teacher, 2015)
This study was motivated by Hunt and Beglar’s (2002) approaches to teaching vocabulary in which they proposed seven principles of teaching vocabulary. Based on these principles, a questionnaire consisting of 24 four-point Likert scale items on vocabulary teaching practices, and an open-ended item which sought information about problems in teaching vocabulary was developed. The participants were English educators from different countries drawn from an online survey using a questionnaire through LinkedIn groups such as Applied Linguistics, ESL Teacher Professionals, iTeach English and Group-digests. The participants were invited to respond to the questionnaire voluntarily following a web link of the questionnaire in SurveyMonkey.com. The findings show that there were interesting differences of practice in teaching vocabulary with respect to Hunt and Beglar’s seven principles across teaching experiences of the participants, school levels, and learner status. Further examination of the participants’ written responses to challenges in teaching vocabulary indicate that retention and motivation were the most frequently mentioned problems they had in teaching vocabulary.